Thoracoabdominal flap for locally advanced breast tumor reconstruction in a patient with BRCA1 mutation - Danilo Rafael da Silva Fontinele; Ana Lúcia Nascimento Araújo; Rodrigo José de Vasconcelos Valença; Sabas Carlos Vieira (Revista Brasileira de Cirurgia Plástica, 2019)
This case report describes the application of the thoracoabdominal flap technique after locally advanced tumor mastectomy in a patient with breast cancer 1 (BRCA1) mutation. The mastectomy included resection of nearly the entire left pectoralis major muscle, with homolateral axillary lymphadenectomy and reconstruction of the large chest wall defect with a fasciocutaneous thoracoabdominal flap based on the posterior intercostal arteries.